El proceso de amparo en el Perú: antecedentes, desarrollo normativo y regulación vigente - Abad Yupanqui, Samuel B. (2015)
In Peru, the amparo process is the most widely used constitutional process, and   one of the most important ones. For that reason, there is a strong need to analyze in detail this emblematic legal form, as the next questions should be answered: has the amparo process always hadthe same regulation in Peru? Is there only onetype of amparo process? What is the importance of the Constitutional ProcedureCode and the Constitutional Court regarding this process?In this article, the author conducts the mentioned analysis in a remarkable way, providing answers to those and other questions from a historic and legal point of view.